Paleomagnetic constraints on an Archean–Paleoproterozoic Superior–Karelia connection: New evidence from Archean Karelia - Mertanen, S.; Korhonen, Fawna (Elsevier BV, 2011)
Charno–enderbitic granitoids in the Karelia craton of the Fennoscandian shield have been studied paleomagnetically. The characteristic remanence component has a steep negative inclination and is interpreted to record magnetization at a maximum age of 2684 ± 2 Ma. Consistently stable results were obtained from 12 sites in the Koitere area, corresponding to regions with high positive magnetic anomalies and high remanence intensities. Petrographic studies, coupled with rock magnetic investigations, indicate that the remanence resides in fine SD/PSD magnetite grains formed during Neoarchean clinopyroxene alteration. Cross-cutting vertical/subvertical Paleoproterozoic dolerite dykes suggest that the Koitere granitoids are in their original orientations and were not affected by Svecofennian deformation at ca. 1.9–1.8 Ga.The Koitere granitoids have an opposite polarity compared to the steep positive inclination remanence direction of the previously studied ca. 2.63 Ga Varpaisjärvi enderbites and granulites. The data from Koitere and Varpaisjärvi imply that at ca. 2.7–2.6 Ga the Karelia craton was located at high latitudes of 80–60°, whereas previous paleomagnetic data from ca. 2.5 Ga formations in the Vodlozero terrane in NW Russia indicate a near-equatorial position.Comparison of paleomagnetic data from the Koitere and Varpaisjärvi granulite-grade rocks with rocks of similar age in the Superior craton shows that at ca. 2.7–2.6 Ga the Superior and Karelia cratons were located at high latitudes and in close proximity, although the present data cannot demonstrate that the cratons were amalgamated. However, during the Archean–Paleoproterozoic transition at ca. 2.50 Ga both cratons experienced significant rotation and drifting to near-equatorial paleolatitudes, suggesting that the Superior and Karelia cratons may have been attached at that time.